Suitability of ligno-cellulosic particles of Prosopis cineraria (L.) Druce for fabrication of particle boards - Kumar, Anil; Ganguly, Sauradipta; Dutt, Hirdesh; Poonia, Pawan Kumar; Rajawat, B.S.; Khali, D.P. (Indian Journal of Agroforestry, 2020)
The present study was conducted to investigate the suitability of lingo-cellulosic particles of Prosopis cineraria (Khejri) as raw material for fabrication of particle boards. The particle boards were made using 8, 10 and 12% Phenol Formaldehyde resin and subsequently hot pressed at 21 kg cm-2 for 12 minutes. The physical and mechanical properties of the particle boards hence formed, met the requirements of Indian Standard specification IS: 3087 (1985) at different resin contents. However, the swelling of the board was found to be higher than the specified limit as per Indian Standard IS: 3087 at 8 and 10% resin contents which can be further controlled by seizing it with paraffin wax. Boards made with 12% resin content met with the requirements of the standard. The percentage of resin used in manufacturing the particle boards had some notable impacts on improving the mechanical and physical properties of the board. The results of the study indicated in favour of utilisation of lops and tops (lingo-cellulosic particles) of P. cineraria for its efficient use for the fabrication of particle boards at 12% resin content.